2019
DOI: 10.1177/1747021819840583
|View full text |Cite
|
Sign up to set email alerts
|

Commission errors with forced response lag

Abstract: It is often necessary to retrieve intentions once a certain cue occurs in the environment. However, such prospective memory (PM) tasks can also be erroneously recalled even though they are no longer relevant and may result in commission errors. According to the dual mechanism account, commission errors occur because the intention is spontaneously retrieved, and there is a subsequent failure to suppress the associated action, resulting in erroneous instant execution. In three experiments, we tested whether fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…For instance, aftereffects increased under high cognitive control demands (divided attention) during finished phases (e.g., Schaper & Grundgeiger, 2017) or when participants showed impaired cognitive control abilities (e.g., Scullin et al, 2011). Recently, Schaper and Grundgeiger (2019) argued that similar effects observed following the cancellation of an encoded PM task might not necessarily reflect failed response suppression. That is, providing time for response suppression after encountering a no-longer-relevant PM cue did not reduce commission errors in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, aftereffects increased under high cognitive control demands (divided attention) during finished phases (e.g., Schaper & Grundgeiger, 2017) or when participants showed impaired cognitive control abilities (e.g., Scullin et al, 2011). Recently, Schaper and Grundgeiger (2019) argued that similar effects observed following the cancellation of an encoded PM task might not necessarily reflect failed response suppression. That is, providing time for response suppression after encountering a no-longer-relevant PM cue did not reduce commission errors in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Some attribute the occurrence of aftereffects to features of the experimental paradigm, like confusion of participants about the finished task instructions, the proximity of response buttons for PM and ongoing-task responses, or to participants lacking cognitive resources for postactional processing to actively disengage from a completed intention (see Penningroth, 2011). Although Schaper and Grundgeiger (2019) recently suggested that encountering no-longer-relevant PM cues might prompt participants to erroneously form an intention to perform the already completed PM task again, leading to commission errors, it seems unlikely that aftereffects of completed intentions can be explained solely by these factors. They might, however, nevertheless contribute to the occurrence of aftereffects.…”
Section: Alternatives and Extensions Of The Retrieval Accountmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, there is growing evidence that, under conditions of heavy cognitive load or distraction, participants may continue to perform a previously planned intention when they no longer have to do so ( Boywitt et al, 2015 , Experiment 1; Matos et al, 2020 ; Pink & Dodson, 2013 ). These memory failures, termed as PM commission errors, are thought to occur when participants spontaneously notice the PM cue and fail to inhibit PM execution ( Bugg et al, 2016 ; Scullin et al, 2012 ; Schaper & Grundgeiger, 2019 ). This can be observed, for example, in some studies ( Boywitt et al, 2015 , Experiment 1; Matos et al, 2020 ; Pink & Dodson, 2013 , Experiments 1a and 1b) adding tone-monitoring, digit-monitoring or counting recall tasks to an LDT in which focal PM cues were embedded (i.e., pressing a key when target words were detected).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we argue that the late-onset response slowing reflects a response verification process. In line with Schaper and Grundgeiger (2019), we assume that spontaneously retrieving the no-longer-relevant PM response and exerting control over intention execution to prevent making a commission error in a PM REPEATED trial elicits an experience of a discrepancy, which then triggers a search in memory to verify whether interrupting the PM response was correct or not. This notion is further corroborated by preliminary evidence of a negative correlation between initial movement deflection and the peak of response slowing in our exploratory analysis, which suggests that the verification process seems to be more time-consuming the further the no-longer-relevant PM response had been performed initially.…”
Section: Spontaneous Retrieval Of Completed Intentionsmentioning
confidence: 97%